Cytotoxic Compounds from Endemic Arnebia purpurea - Harput, U. Sebnem; Duman, Hayri; Bilgili, Bilgehan; Güvenalp, Zühal; Saraçoğlu, İclal; Yuzbasioglu, Merve; Toth, Gabor; Demirezer, L. Omur; Simon, Andras; Kazaz, Cavit; Kuruuzum-Uz, Ayse (SAGE Publications, 2015)
Phytochemical studies of the roots and aerial parts of endemic Arnebia purpurea S. Erik & H. Sumbul resulted in the isolation and characterization of four naphthoquinones [isovalerylalkannin (1), α-methyl- n-butanoyl alkannin (2), acetylalkannin (3), and alkannin (4)], a triterpene derivative [3- O-acetyl-oleanolic acid (5)], a steroid [β-sitosterol (6)], three flavonoid glycosides [isorhamnetin-3- O-rutinoside (7), kaempferol-3- O-rutinoside (8), kaempferol 3- O-(5″-acetyl) apiofuranoside 7- O-rhamnopyranoside (9)] and a phenolic acid [rosmarinic acid (10)]. 3- O-Acetyl-oleanolic acid, isorhamnetin-3- O-rutinoside, kaempferol-3- O-rutinoside, and kaempferol 3- O-(5″-acetyl) apiofuranoside 7- O-rhamnopyranoside are reported from an Arnebia species for the first time. Cytotoxic activities on L929 murine fibrosarcoma cell line of the isolated compounds were investigated using MTT assay. Naphthoquinones (1–4) showed intermediate cytotoxic activity in comparison with the standard, doxorubicin.
Keywords: Fibrosarcoma; Plant Components, Aerial; Boraginaceae; Antineoplastic Agents, Phytogenic; Plant Roots; Mice; Cell Line, Tumor; Animals; Naphthoquinones; 16. Peace & justice; 3. Good health